2004
DOI: 10.1007/s00508-004-0258-y
|View full text |Cite
|
Sign up to set email alerts
|

Endurance performance of the elderly mountaineer: Requirements, limitations, testing, and training

Abstract: Life expectancy has markedly increased during recent decades, resulting in a growing number of older individuals. Many of these elderly are turning to mountain sports activities in search of fun and new challenges. Although the scientific community has taken broad interest in the ageing process and how it affects physical and mental performance, little attention has focused on the elderly mountaineer. Mountain sports demand a relatively high degree of physical fitness and, because fitness and health decline wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 73 publications
1
54
0
2
Order By: Relevance
“…This is in line with findings from sports medicine (Burtscher 2004). According to constraint research, the perception of a constraint to outdoor recreation, such as the perceived lack of skill, does not necessarily result in non-participation in an activity.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This is in line with findings from sports medicine (Burtscher 2004). According to constraint research, the perception of a constraint to outdoor recreation, such as the perceived lack of skill, does not necessarily result in non-participation in an activity.…”
Section: Discussionsupporting
confidence: 86%
“…This was reasoned by the fact that studies on physical activity and ageing conducted in different contexts revealed the consistent finding that vigorous activities, like walking uphill (Ainsworth et al 2000), decrease strongly with age (Colley et al 2011;Troiano et al 2008). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is proven by more than 4 billion people per year who are exposed to such hypoxia as aircraft passengers and for other reasons [15,16] and by billions of smokers with a CO haemoglobin concentration of 5% that corresponds to hypoxia of about 15%. An increased risk for altitude-respectively hypoxia-related disturbances arises above 3,000 m (<14.5% O 2 ) for persons without severe pre-existing diseases [15,17].…”
Section: Introductionmentioning
confidence: 99%